Reaksi Pasar Atas Penerbitan Sukuk (Studi Pada Emiten Saham Penerbit Sukuk Periode 2008-2012) - Fatimatuzzahra, Vita; Herlambang, Leo (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Issuance of SukÃ»kâs corporation, it can be an opportunity for many companies toÂ become proponent necessity for funding and business expansion. SukÃ»k publicationÂ announcement is an information for investors in order to assess it based on their investmentÂ decisions. In order to get the investment decisions, investors often based on the signals thatÂ had been given by the company. That signal can caused the changes of demand andÂ supplyâs shares. This study aims to find out the reaction of the stock from the SukÃ»kÂ publication as indicated by the presence of abnormal returns around the date ofÂ publication and the Trading Volume Activity (TVA) difference which is occured before andÂ after SukÃ»k publication.This study uses event study approach, it carries out on 11 issuer stock of SukÃ»k publisherÂ which is listing in Indonesia Stock Exchange period : 2008-2012. This study also usesÂ observation period for 81 days, they are t - 10 (70 days before publication), t - 0 (event date)Â and t +10 (10 days after publication). The hypothesis calibration of this thesis uses a oneÂ sample t - test and paired t - test.The results of this study is based on a statistical test with a significance level (Î±) = 5 %resulted AAR which was in a significantly positive on t - 2 at 0.03711 and significantly negativeat t +9 of 0.03. In contrast with TVA, the statistic results showed probability value of 0.026,which means there is a significant different of trading volume activity before and after ofSukÃ»k publication. The lack of information about SukÃ»k also caused there is significant AARreaction only in some poriods of observation and significant negative TVA .